Stress Management And Employee Performance Among Health Information Managers In Central Hospital Ughelli, Delta State, Nigeria - ugo CHUKS okolie (Indonesian Journal Of Business And Economics, 2022)
Occupational stress and burnout have an undeniable negative impact on organizational performance. In light of this, this study examined the impact of stress management on employee performance among health information managers at Central Hospital Ughelli in Delta State. The study used a survey design, and the research instrument was a questionnaire, with 25 participants deemed usable. The information gathered was analyzed and presented in frequency tables using simple percentages. The study findings showed that the majority of the respondents agreed to improper time management and work overload as the major causes of stress in workplace and concluded that there are several factors causing stress among health information management staff in Central Hospital Ughelli, Delta State Nigeria. The study therefore recommends, among other things, that hospital management should assist their staff by providing adequate technology to reduce workload and work related stress.